Identifikasi Kompetensi Emosional dan Sosial Bagi Anggota DPR RI yang Secara Efektif Terpilih Lebih dari Satu Kali oleh Rakyat: Studi Kasus pada Anggota DPR RI Periode 2019-2024 - Akbar, Fauzi; Kusumastuti, Dyah; Mulyani, Sri Rochani (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
From the main duties of members of the DPR RI and how members of the DPR RI can be elected for several periods as well as the results of interviews with members of the DPR RI who have been elected more than once. From table 1 it can be analyzed that with a total of 11 commissions and the average number of members of each commission is 53 members. So from the data obtained, the number of members of the DPR RI who were elected for more than 1 period still dominates in the 2019-2024 elections. Of the 575 elected members of the DPR RI, as many as 286 people or 49.74 percent are non-incumbents. (only once elected) as many as 298 people or 50.26 percent are incumbents (elected more than once). Of course, for members of the DPR who have been elected several times, they have abilities that can be realized and felt by the people who voted for them. SWOT Analysis Identification of Social and Emotional Competencies for Members of the Indonesian House of Representatives who were Effectively Elected by the People More than once (Study on Members of the Indonesian House of Representatives for the 2019-2024 Period) In analyzing the data collected, using SWOT analysis (Strengthness, Weakness, Opportunities, Threatment). The basic concept of this SWOT approach is to first identify the strengths and weaknesses as well as opportunities and threats so that the problems faced, how to achieve them and the actions that need to be taken to maximize strengths and seize existing opportunities and overcome weaknesses and threats can be identified. As for the factors of social competence and emotional competence for members of the DPR RI who have been effectively elected more than once. Emotional Self Awareness, describes how members of the DPR RI understand their own emotions so that they do not have an impact on others. The results of interviews with sources at the Democratic Party, Golkar and PDIP can explain that as a member of the DPR, one must be able to have self-comfort, the ability to think positively, recognize one's weaknesses to be able to control oneself. The second dimension in this study is self-management, with three measurements, namely self-control, achievement orientation and positive outlook. Self-control measures the efforts of members of the DPR RI in facing work challenges and criticism, the results of interviews that have been conducted explain that challenges must be faced, for that it is important for members of the DPR RI to equip themselves with knowledge and information in order to be able to face work challenges. The third dimension in this research is Relationship Management. Where relationship management is measured by four measurements, namely Communication to Influence, Conflict Management, Inspirational leadership and Negotiation. In the Communication to Influence measurement, analyzing the efforts of members of the DPR RI who were elected more than once in building communication with other people in overcoming problems in order to achieve an agreed solution .The fourth dimension in this study is Social Awareness, with four measurements, namely Empathy, Teamwork, Organizational awareness and National Adhesives. The results of the interview explained that as a member of the DPR RI, it is necessary to understand the problems presented by other people, receive messages with a calm attitude so that with a calm attitude they can find the best solution.